No-tillage curly lettuce cultivated under different spacings - Antonio M. Cecconello; Emerson Trogello; Jolcemar Ferro; Otavio B. Rossato (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The use of appropriate cultural practices is important for the sustainability of the production system. This study aims to evaluate the agronomic performance of lettuce cultivar ‘Mônica’, during two crop cycles, at the Instituto Federal Catarinense, Campus of Concórdia, SC, Brazil. Two experiments were conducted in the field, arranged in randomized block design, in a 3 x 2 factorial scheme, evaluating the effects of three spacings (0.20 × 0.20, 0.25 × 0.25 and 0.30 × 0.30 m), associated with two planting systems (conventional and no-tillage with millet), with four repetitions in the first cycle and five in the second. At 39 and 44 days after transplanting, six plants were harvested in the first and in the second cycles, respectively. Soil temperature, fresh and dry mass of the spontaneous plants, dry mass of roots, plant diameter, number of marketable leaves, fresh and dry mass of the plants were evaluated. Lettuce cultivated under no-tillage at larger spacings resulted in higher yield per plant, but higher yield per area was observed at smaller spacing. No-tillage reduced spontaneous plants and soil temperature in the West of Santa Catarina.